2002
DOI: 10.1016/s0168-6445(02)00091-8
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae and cholera: out of the water and into the host

Abstract: The facultative human pathogen Vibrio cholerae can be isolated from estuarine and aquatic environments. V. cholerae is well recognized and extensively studied as the causative agent of the human intestinal disease cholera. In former centuries cholera was a permanent threat even to the highly developed populations of Europe, North America, and the northern part of Asia. Today, cholera still remains a burden mainly for underdeveloped countries, which cannot afford to establish or to maintain necessary hygienic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
241
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(241 citation statements)
references
References 96 publications
0
241
0
Order By: Relevance
“…In natural waters the bacterium can be present in both a free-living state (Worden et al, 2006) or attached to copepods, zooplankters and algae (Lipp et al, 2002;Reidl & Klose, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In natural waters the bacterium can be present in both a free-living state (Worden et al, 2006) or attached to copepods, zooplankters and algae (Lipp et al, 2002;Reidl & Klose, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, within the 01 serogroup classification, cholera cases are identified as being of a particular biotype (classical or El Tor) and of a particular serotype (Inaba or Ogawa, and very rarely Hikojima). Cholera biotypes are distinct phenotypes that differ with respect to the severity of their infections (and consequently their infectionto-case ratios), ability to survive outside the human host and seasonality patterns (Woodward & Mosley 1972;Glass et al 1982;Reidl & Klose 2002;Koelle et al 2005a). Serotypes differ from one another only with respect to antigenic determinants that are present on their O-antigen capsule.…”
Section: Introductionmentioning
confidence: 99%
“…Several culturedependent and -independent studies have confirmed the ubiquity of vibrios, and suggested Vibrio populations generally comprise approximately 1% (by molecular techniques) of the total bacterioplankton in estuaries (19), in contrast to culture-based studies demonstrating that vibrios can comprise up to 10% of culturable marine bacteria (20). Clearly, vibrios are ubiquitous and abundant in the aquatic environment on a global scale, including both seawater and sediment (19,(21)(22)(23)(24)(25), and repeatedly shown to be present in high densities in and on marine organisms, such as corals (26), fish (27-29), mollusks (30), seagrass, sponges, shrimp (28, 31), and zooplankton (16,17,28,32,33).During dives of the deep-sea submersibles Alvin and Nautile in 1999 along the East Pacific Rise, southwest of the Mexico coast, samples of water surrounding sulfide chimneys of a hydrothermal vent community were collected and four mesophilic bacterial isolates were cultured, which were subsequently tested for phenotypic traits, including growth on V. cholerae selective thiosulfate-citrate-bile-salts-sucrose (TCBS) agar (Oxoid). The sampling locations from where these four mesophilic bacteria were isolated are described in Table 1.…”
mentioning
confidence: 99%